Celebrating the generation of architectural ideas: tracing the lineage of Southeast Asian temples - Beynon, D.; Datta, Sambit (Society of Architectural Historians Australia and New Zealand, 2005)
From its early beginnings in the fifth century, the Brahmanic/Hindu tradition created a rich body of temples which spread across India and influenced temple building in Southeast Asia. The legacy of this ancient diasporic movement remains celebrated today in the admiration of Southeast Asian monuments such as Angkor Wat and Prambanan. However this architecture evolved over time through a process of long experimentation with philosophies, world-views, and methods. The architectural forms of such monuments have obvious Indian antecedents but the process of their development into distinctive indigenous forms remains difficult to ascertain. This is due both to the lack of textual accounts from the earliest Southeast Asian civilisations and because their architectural remains are fragmented or heavily eroded. This paper draws on a research project that pieces together fragments of evidence from diagrams and canonical descriptions to photogrammetry of temples in India and Southeast Asia. The intention of this is to establish the degree to which Southeast Asian temples are attributable to Brahmanic/Hindu lineage and influence. It will focus on the role of the early Southeast Asian temple site of Sambor Prei Kuk (lsanapura) in Cambodia. Comparing the relationships between cosmology, geometry and physical form in this earlier sites with both Indian and developed Southeast Asian models, it is intended that its generative role within Southeast Asian architectural historiography can be clarified and more fully celebrated.